The moral dilemma of obstetric violence: A meta-synthesis - Li, Wei (Nursing ethics, 2025)
Although the global healthcare system is paying increasing attention to obstetric violence, this form of gender-based violence during childbirth remains a serious issue. The primary objective of this comprehensive study is to explore the experiences and needs of women subjected to obstetric violence on a global scale. A systematic search was conducted in December 2024 across the Web of Science, Embase, PubMed, and CINAHL databases to identify eligible studies. Data synthesis was performed using the three-stage thematic and content analysis method. A total of 39 eligible qualitative studies were included in this review. Thematic synthesis identified 6 themes and 17 sub-themes: (1) Obstetric Violence Types; (2) Gaslighting Effect: The Authoritative Position of Healthcare Providers; (3) Stigmatization and Discrimination Experienced by Women; (4) Who is Normalizing Obstetric Violence? (5) Substandard Medical Institutions; (6) Trauma Induced by Obstetric Violence. Obstetric violence continues to persist in various countries and regions. Women have endured various forms of obstetric violence, with their autonomy and rights to informed consent being severely compromised. They have experienced neglect and abandonment by healthcare providers, and face discrimination and differential treatment due to factors such as race, socioeconomic status, age, and culture. The primary cause of obstetric violence is the unequal power dynamics between healthcare providers and women, with the authoritative position of healthcare providers leading to a lack of communication and recognition between both parties.